Level measurement for saline with a small surface area using high frequency electromagnetic sensing technique. (April 2017) - Yang, Tiemei; Zhao, Qian; How, Kin Yau; Xu, Kai; Lu, Mingyang; Xie, Yuedong; Yin, Wuliang
Abstract: Liquid level measurement is an important requirement in many industrial applications. Previously, an inductance method was developed for liquid with an infinite surface area; but the technique is not suitable for liquid with a small surface area, in which case, the analytical approach we developed previously is no longer valid. In this paper, we present a novel approach based on the high frequency electromagnetic induction technique for the measurement of liquid level with a small surface area. To understand the electromagnetic interaction between the proposed sensor and the liquid under measurement, a FEM solver in the thick skin regime is developed for the modeling. The developed 3D solver has the capability to simulate liquid with an arbitrary surface area. An FPGA based instrument has been developed for this measurement application and experiments were conducted in our laboratory. Sensitivity analysis and error analysis have been carried out for selecting optimal coil configurations. Experiment results have shown that under optimal conditions, the level accuracy is within 0.5 mm. This confirmed the validity and effectiveness of our proposed approach based on the high frequency electromagnetic sensing principle.